A note on the Generalized Bernoulli and Euler Polynomials (European Journal of Pure and Applied Mathematics, 2017)
In this paper we use probabilistic methods to derive some results on the generalized Bernoulli and generalized Euler polynomials. Our approach is based on the properties of Appell polynomials associated with uniformly distributed and Bernoulli distributed random variables and their sums.Â